PENGARUH MODEL RECIPROCAL TEACHING TERHADAP KEMAMPUAN PEMAHAMAN MATEMATIKA SISWA SEKOLAH DASAR - Nur Azizah Nasution; Arfin Hasibuan (Sasangga: Jurnal Pendidikan dan Pembelajaran, 2025)
This study aims to examine the effect of the Reciprocal Teaching model on elementary students’ mathematical understanding at Elementary School Negeri 1501 Hurung Jilok. The study employed a quantitative approach using a quasi-experimental one-group pretest–posttest design. The participants were all fifth-grade students in one class. Data were collected through a mathematical understanding test administered before and after the implementation of the Reciprocal Teaching model. Data analysis was conducted using descriptive statistics and a paired sample t-test after meeting the required assumptions. The findings reveal a difference in students’ mathematical understanding before and after the implementation of Reciprocal Teaching. These results indicate that mathematics instruction emphasizing dialogic and reflective strategies through Reciprocal Teaching is associated with changes in students mathematical understanding. This study provides empirical evidence supporting the use of the Reciprocal Teaching model as an alternative approach to mathematics instruction in elementary schools.